2015
DOI: 10.1186/s40550-015-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

Presence of arsenic in Sri Lankan rice

Abstract: Background: Arsenic and heavy metals are implicated in causation of CKDu among farmers in dry zone of Sri Lanka. Rice has been identified as a major source of arsenic in research carried out in other countries. We analyzed 120 samples of new improved varieties (NIVs) and 50 samples of traditional varieties (TV) of rice for total arsenic content. Findings: Rice cultivated in Sri Lanka is contaminated with arsenic. Agrochemical dependent NIVs contain considerable amount (20.6-540.4 μg/Kg) of arsenic. There is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 24 publications
0
38
0
2
Order By: Relevance
“…Williams et al (2007) reported that the baseline inorganic As levels in rice are tenfold higher compared to other cereals. Although the groundwater and surface water arsenic levels are insignificant in Sri Lanka (Chandrajith et al 2011; Nanayakkara et al 2014), some studies highlighted alarming higher levels (21–540 µg/kg) of As in rice from Sri Lanka (Jayasumana et al 2015). This enriched As in rice was attributed to the application of contaminated fertilizer and pesticides in paddy cultivation.…”
Section: Resultsmentioning
confidence: 99%
“…Williams et al (2007) reported that the baseline inorganic As levels in rice are tenfold higher compared to other cereals. Although the groundwater and surface water arsenic levels are insignificant in Sri Lanka (Chandrajith et al 2011; Nanayakkara et al 2014), some studies highlighted alarming higher levels (21–540 µg/kg) of As in rice from Sri Lanka (Jayasumana et al 2015). This enriched As in rice was attributed to the application of contaminated fertilizer and pesticides in paddy cultivation.…”
Section: Resultsmentioning
confidence: 99%
“…Ochratoxin A [225], aluminium, fluorine [226] heavy metals; iron and lead [227] and arsenic [228]. However, these findings were later challenged by other studies and the cause still remains unresolved.…”
Section: E) Exposure From Water Used In Medical Treatmentsmentioning
confidence: 99%
“…Scientific research has found a number of causes for CKDu, of which one was As and Cd contamination (Bandarage, 2013). Jayasumana et al (2015) reported considerable amount (20.6-540.4 μg/Kg) of arsenic in rice, which is depend on the fertilizers and pesticides used during the cultivation.…”
Section: Introductionmentioning
confidence: 99%